Cause of Entrapment Syndromes in Gastrocnemius Muscle: A Prospective Study - Shinde Amol A.; Patel Dinesh K.; Bharambe Vaishaly K. (Issues and Developments in Medicine and Medical Research Vol. 5, 2022)
Gastrocnemius injuries have been one of the leading causes of calf injuries. Medial head of gastrocnemius is more commonly involved. Accessory heads of gastrocnemius have given rise to entrapment syndromes in the popliteal fossa. 60 formalin embalmed lower limbs were meticulously dissected. Any variation in number of heads, origin, insertion and nerve supply of gastrocnemius muscle is noted. Popliteal artery entrapment syndrome has been reported due to aberrant course of popliteal artery or accessory heads of gastrocnemius or plantaris muscle compressing a normal popliteal artery. Bilateral variation is seen in 10% cadavers. Three (6.66%) and four (8.33%) headed gastrocnemius muscles are reported. Knowledge of additional heads of gastrocnemius is important while autografting and using imaging techniques for entrapment syndromes. During imaging exams for polpliteal entrapment syndromes and neurovascular compression, the radiologist will benefit from learning about the accessory heads of the gastrocnemius.